Relational Contracting Conceptual Model for Public Sector Construction Organisations: An Indian Context (Construction Economics and Building, 2018)
Adoption of relational contracting in public sector construction organisations is more difficult than in private sector organisations due to the inherent rigidity of public sector. Therefore, implementation of the relational contracting processes should be treated as an organisational change management process in public sector organisations. The purpose of this paper is to develop a relational contracting conceptual model (RCMM) by integrating success factors for positive change management in public sector organisations. A qualitative research methodology comprising two rounds of expert interviews was used. The first round of interviews was conducted to gauge the present level of relational contracting in public sector construction organisations. The second round of interviews was conducted to validate the relational contracting conceptual model by integrating success factors of change management in public sector organisations. The relational contracting model highlighted the importance of a need to develop a vision for partnering, stakeholder analysis and consensus building among them, empowerment of operational level employees and their participation in plan execution, time bound review meetings of top management on site to show commitment, resolution of disputes and fast decision making along with publication of the performance reports. The paper presents a critical insight on relational processes of public sector construction organisations in India in the context of organisational change management model which has not been the focus in majority of the previous research studies.